An emerging paradigm: a strength-based approach to exploring mental imagery - Macintyre, Tadhg E.; Moran, Aidan P.; Collet, Christian; Guillot, Aymeric (Frontiers in Human Neuroscience, 2013)
Mental imagery, or the ability to simulate in the mind information that is not currently perceived by the senses, has attracted considerable research interest in psychology since the early 1970s. Within the past two decades, research in this field – as in cognitive psychology more generally - has been dominated by neuroscientific methods that typically involve comparisons between the imagery performance of participants from clinical populations with those who exhibit apparently normal cognitive functioning. Although this approach has been valuable in identifying key neural substrates of visual imagery, it has been less successful in understanding the possible mechanisms underlying another simulation process, namely, motor imagery or the mental rehearsal of actions without engaging in the actual movements involved. In order to address this oversight, a “strength-based” approach has been postulated which is concerned with understanding those on the high ability end of the imagery performance spectrum. Guided by the expert performance approach and principles of ecological validity, converging methods have to potential to enable imagery researchers to investigate the neural ‘signature’ of elite performers, for example. Therefore, the purpose of this paper is to explain the origin, nature and implications of the strength-based approach to mental imagery. Following a brief explanation of the background to this latter approach, we highlight some important theoretical advances yielded by recent research on mental practice, mental travel and meta-imagery processes in expert athletes and dancers. Next, we consider the methodological implications of using a strength-based approach to investigate imagery processes. The implications for the field of motor cognition are outlined and specific research questions, in dynamic imagery, imagery perspective, measurement, multi-sensory imagery and metacognition, that may benefit from this approach in the future are sketched briefly.